The Role of Battery Energy Storage in Colombia’s Sustainable Energy Transition: A Socio-Ecological and Economic Perspective - Martínez, Fredy; Hernández, César; Giral, Diego (Journal of Ecohumanism, 2024)
This paper explores the integration of Battery Energy Storage Systems (BESS) in Colombia’s power grid as a socio- environmental solution for the country’s renewable energy transition. Given Colombia’s increasing reliance on solar energy, the intermittency of this source presents challenges that demand sustainable energy storage solutions. This study analyzes the role of BESS not only in technical terms but also from an eco-humanistic perspective, incorporating environmental, economic, and social justice dimensions. Through an interdisciplinary approach, we examine the potential for BESS to support energy democratization, reduce dependence on fossil fuels, and foster inclusive energy policies. Additionally, the paper discusses regulatory challenges, economic feasibility, and the environmental impact of BESS deployment in Colombia. Finally, we present policy recommendations to ensure a just and sustainable energy transition.